Assessing Faculty Members’ Levels of Information-Seeking Motivation:A Case of MSRT and Medical Universities of Iran - Negahban, Mohammad Bagher (Journal of Information and Knowledge, 2016)
This study assesses the faculty members’ levels of motivation for seeking and collecting multi-purpose information in the Iranian contexts of Ministry of Science, Research and Technology (MSRT) and Medical universities (Ministry of Health and Medical Education). The randomly-selected respondents included 140 from MSRT and 105 from Medical universities. The data collection and analysis instruments consisted of a questionnaire and descriptive statistics. Results revealed higher levels of information-seeking motivation for MSRT faculty members pertaining to their research, visibility among peers, departmental promotions, project reviews, knowledge update, professional competence, and educational pursuit. The faculty members of Medical University had higher motivation for information-seeking to meet competition, recognition, and personal factors.